Life cycle assessment (LCA) of portland composite cement (PCC) 50 kg papercraft bag at PT. Semen Padang. Issue 1 (January 2021) - Panggabean, T; Aziz, R; Dewilda, Y
Abstract: PT. Semen Padang produces several cement types, including PCC, with a total production of up to 6, 568, 354 tons in 2018. PCC production reached 54% of the total, where the size of 50 kg bag dominates the production with 93%, and the use of papercraft bags as the cement packaging is 78.39%. This research aims to analyze the environmental impacts of the production of 1 ton of PCC 50 kg paper craft bag using the LCA method. The gate-to-gate approach applies as the boundary, ranging from raw mill till packing unit. The impact assessment method uses IMPACT 2002+ to assess the environmental impact of the production. The result shows that the highest environmental impacts are global warming, non-renewable energy, and respiratory inorganics, with the value amounted to 0.10884252 Pt. The process of calcination and coal used in the kiln, packaging transport by diesel-powered trucks, and electricity use is the main contributor to the impact value. In order to improve the PCC production, it is recommended to have an alternative fuel on the kiln unit using rice husks or Mischantus giganteus .